2010
DOI: 10.1002/eji.200940221
|View full text |Cite
|
Sign up to set email alerts
|

HAX1 deficiency: Impact on lymphopoiesis and B‐cell development

Abstract: HAX1 was originally described as HS1-associated protein with a suggested function in receptor-mediated apoptotic and proliferative responses of lymphoid cells. Recent publications refer to a complex and multifunctional role of this protein. To investigate the in vivo function of HAX1 (HS1-associated protein X1) in B cells, we generated a Hax1-deficient mouse strain. Targeted deletion of Hax1 resulted in premature death around the age of 12 wk accompanied by a severe reduction of lymphocytes in spleen, thymus a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 45 publications
0
35
0
1
Order By: Relevance
“…Hax1 -/-bone marrow cells show a decreased number of B220 1 cells HAX1 deletion dramatically decreased the number of bone marrow cells, 8,29 among which the overall cell type distribution was only marginally affected (i.e., a trend toward a decreased percentage of lymphocytes) ( Figure 1a). However, within the lymphocyte population, we found that the percentage of B220 1 cells decreased significantly (Figure 1b), which suggests impaired lymphopoiesis throughout the development of B220 1 cells.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Hax1 -/-bone marrow cells show a decreased number of B220 1 cells HAX1 deletion dramatically decreased the number of bone marrow cells, 8,29 among which the overall cell type distribution was only marginally affected (i.e., a trend toward a decreased percentage of lymphocytes) ( Figure 1a). However, within the lymphocyte population, we found that the percentage of B220 1 cells decreased significantly (Figure 1b), which suggests impaired lymphopoiesis throughout the development of B220 1 cells.…”
Section: Resultsmentioning
confidence: 99%
“…28 We generated a mouse model in which we deleted exons 2 and 3 of HAX1 on chromosome 3 and abolished the production of both splice variants; this model was used to demonstrate the crucial function of HAX1 in B cell development and in hematopoietic stem cell homeostasis maintenance. 29 Additionally, as described in detail by Chao et al, 8 HAX1 deletion led to death at the age of 12 weeks; this premature death was caused by a loss of motor coordination, leading to a failure to drink and eat. Here, we aimed to explain the reduced number of B cells in more detail, and we asked whether the general viability of the bone marrow B progenitor cells and of the splenic B cells might be affected by the proposed anti-apoptotic function of HAX1.…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations